Impact of periodontitis on the quality of life of obese patients: a systematic review (Research, Society and Development, 2022)
Introduction: Obesity is a chronic disease and has been associated with periodontal disease. This is characterized by a subclinical chronic inflammation that can exacerbate other chronic inflammatory diseases such as periodontitis. Objective: It was to assess whether periodontal diseases impact the quality of life related to oral health in obese patients. Materials and Methods: This systematic review followed the National Health Service Center for Reviews and Dissemination (NHS, 2001) guidelines and preferred reporting items for systematic reviews and meta-analyses (PRISMA). A bibliographic search was carried out in PubMed, Scopus and Embase databases. Eligibility criteria were defined in relation to participants, interventions, comparisons, results and study design (PICOS), following PRISMA. Results: This search was classified in Phase I: where the search was carried out, resulting in a total of 44 articles. After reading the titles and abstracts and taking into account the inclusion criteria, a total of 24 articles were discarded. A total of 6 articles were studied, of which 5 articles remained for final analysis (Phase II). Conclusion: The quality of life of obese patients was impacted by the relationship between periodontitis and diet. The risk factors that aggravate periodontal disease and obesity should be better clarified when related to quality of life. Future long-term studies should be conducted relating periodontal disease and quality of life in obese individuals, to explore mediators of changes in quality of life and interactions with other variables, such as comorbidities and body image.